Geometria espacial na EJA: uma proposta de ensino à luz do modelo van Hiele com auxílio do software de geometria dinâmica GeoGebra - Silva, Eber Oliveira (2021)
This dissertation is the result of a study that aims to analyze the challenges and possibilities for the teaching of spatial geometry in Youth and Adult Education (EJA), based on official documents, on EJA conceptions, on theories of thought development. geometric and methodological resources adopted for this teaching. The study begins with the analysis of the legal aspects of EJA and the peculiarities of this modality of Basic Education, highlighting some conceptions, challenges and possibilities for teaching young people and adults today. Next, an approach to van Hiele's theory is made, seeking to understand the development phases of geometric thinking in young and adult students and how geometric concepts should be approached in the teaching and learning process. As an auxiliary resource to the teaching of Spatial Geometry at EJA, a proposal for the use of the GeoGebra software is presented to the area's teachers, with pedagogical aspects for this teaching. In the author's experience as an EJA teacher, what can be seen is that most publications dealing with the teaching of Geometry with the help of GeoGebra, despite the great contributions to teaching, are not motivating for the EJA student, mainly because the vocabulary adopted and the way of approaching the contents are not adequate to the reality of this student. In this sense, this work discusses the need for the teacher to look at the specifics of teaching for young and adult students, considering their interests, expectations, potential, levels of geometric thinking and learning rhythms. Seeking theoretical support in official documents of Basic Education and in authors such as D’Ambrosio (2012); Fonseca (2005); Freire (1996); Gadotti e Romão (2000); Kaleff [et al] (1994); Lorenzato (1995); Nunes, Carraher e Schliemann (2011); among others, seeks to understand the educational aspects of EJA and propose alternatives to improve geometry teaching, so that learning occurs satisfactorily, in compliance with the role of the teacher and the school in providing quality education for young and adult students, as guaranteed by current legislation.